2019
DOI: 10.1016/j.jobcr.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health & Quality of Life in preadolescents with hearing impairment in Uttarakhand, India

Abstract: Background: "Better teeth better health" is a guiding dictum for the 21st century that has been well adopted by WHO and emulated world over by numerous health care agencies. Hence its of paramount importance to assess the impact of oral health on the quality of life. Keeping this in mind the present study was done to gauge the impact of prevalence of dental diseases amongst 9-15 year old institutionalized hearing impaired children in districts of Uttarakhand, India. Materials & methodology: 250 hearing impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
2
8
0
2
Order By: Relevance
“…Similar results were reported in Brazil 32 (42.9%), India (35.32%), 33 and Rwanda (42.4%). 34 A slightly higher prevalence of dental caries was documented in hearing-impaired children in India (56%), 35 Thailand (53.6%), 36 and China (55.9%). 37 Azfar et al reported that over half (51%) of hearing and speech-impaired children in Pakistan had dental caries.…”
Section: Discussionmentioning
confidence: 95%
“…Similar results were reported in Brazil 32 (42.9%), India (35.32%), 33 and Rwanda (42.4%). 34 A slightly higher prevalence of dental caries was documented in hearing-impaired children in India (56%), 35 Thailand (53.6%), 36 and China (55.9%). 37 Azfar et al reported that over half (51%) of hearing and speech-impaired children in Pakistan had dental caries.…”
Section: Discussionmentioning
confidence: 95%
“…Percebeu-se por meio desta revisão que as condições bucais e a percepção dos pacientes surdos em relação à saúde bucal não são adequadas, não por culpa do paciente, mas sim pela falta de diálogo estabelecido, muitas vezes o paciente não compreende o que está sendo realizado ou falado, ou nunca foi ensinado sobre os princípios de educação em saúde bucal (JIN, 2010;OREDUGBA, 2004;PEREIRA, 2017;SINGH, 2019). Nos estudos de Doichinova e Peneva (2013) e Uemura (2004), verificaram que quando ferramentas adequadas de comunicação são estabelecidas, há melhora nas condições bucais dos pacientes, isto mostra a importância do profissional se capacitar para o atendimento do paciente surdo.…”
Section: Discussionunclassified
“…Após a utilização das imagens, o índice de placa foi reduzindo gradativamente até chegar a 14%. Singh et al (2019), avaliou a condição bucal de 250 crianças surdas de 9 a 15 anos, de uma instituição de ensino, dentre as variáveis avaliadas estavam a cárie dentária, anomalias dentofaciais e trauma dentário. A cárie dentária e anomalias faciais foram as condições mais prevalentes, ainda se realizou avaliação da auto percepção de saúde das crianças, dos quais referiram diversos problemas bucais como sangramento gengival, mau hálito, má posição dentária, entre outros.…”
Section: Atendimento Clínicounclassified
“…Dental Surgeons, in addition to having extensive technical and scientific knowledge, need to know a means of communication with their patients. It is important to establish effective communication with the hearing impaired, aiming at better oral health for these patients 11,12 . Blocking communication between the hearing impaired and health professionals represents a significant obstacle for this population.…”
Section: Discussionmentioning
confidence: 99%